Examining the Relationship Between Grit and Foreign Language Performance: Enjoyment and Anxiety as Mediators - Liu, Eerdemutu; Wang, Junju (Frontiers in Psychology, 2021)
The influence of grit on academic performance has been extensively investigated. However, the impact of grit on language performance in EFL contexts is still underexplored. The present study, therefore, investigated the relationship among grit, positive emotion of enjoyment, negative emotion of anxiety and foreign language performance, and how the two emotions mediated the relationship between grit and foreign language performance. A questionnaire encompassing grit scale, foreign language enjoyment scale and foreign language classroom anxiety scale was administered to 697 Chinese high school students, and students’ final exam sores were recorded two weeks after the survey. Results showed that most students concurrently had a moderate level of grit, anxiety and enjoyment. More than half of the students had moderate to high level of grit and foreign language enjoyment and nearly half of the students experienced low to moderate level of foreign language anxiety. Besides, grit was positively correlated to foreign language enjoyment and foreign language performance, but negatively correlated with foreign language anxiety. Foreign language enjoyment was negatively correlated with foreign language anxiety and positively corelated with foreign language performance and foreign language anxiety was negatively correlated with foreign language performance. Finally, it was found that the influence of grit on foreign language performance can be indirectly strengthened by increasing foreign language enjoyment and decreasing foreign language anxiety, and that the mediating effect of foreign language anxiety is stronger than that of foreign language enjoyment.